Gallium-Inducible Transferrin-Independent Iron Acquisition Is a Property of Many Cell Types: Possible Role of Alterations in the Plasma Membrane. (1st April 2005) - Olakanmi, Oyebode; Stokes, John B.; Britigan, Bradley E.
Abstract : Background: We have previously shown that human myeloid cell types can acquire large amounts of iron (Fe) 3+ from low-molecular-weight chelates by a process that is independent of adenosine triphosphate and dramatically increased by gallium (Ga) and other multivalent cationic metals. Methods: To provide further insight into the mechanism responsible and its relevance to other cellular systems, we investigated Fe acquisition from nitrilotriacetic acid (NTA) by several myeloid and nonmyeloid cell lines in the presence and absence of Ga. Results: Most nonmyeloid cells examined exhibited similar ability to acquire Fe from NTA. Ga increased the apparent maximum velocity (Vmax ), with minimal changes in apparent Michaelis constant ( K m), of all cell lines. Both erythrocytes and erythrocyte ghosts acquired Fe from NTA, which increased with Ga exposure, analogous to nucleated cells. However, liposomes made from phospholipids did not exhibit Ga-inducible Fe association. Enzymes that modify surface proteins and carbohydrates did not alter HL-60 cell Fe acquisition. Modifying HL-60 membrane fatty acid content had only a minimal effect. Ga exposure did not change membrane potential or fluidity. However, electron microscopy suggested that Ga alters plasma membrane physical properties. Conclusion: Multivalent cations appear to induce changes in cell membranes that may alter their interaction with Fe 3+ and probably other multivalent cations.